Evidence-based practice, quality improvement, and research: A visual model - Grys, Crystal A (Nursing (Jenkintown, Pa.), 2022)
Understanding the key similarities and differences between quality improvement, evidence-based practice, and research can help improve nursing practice. This article presents visual models to illustrate the relationship between these processes.